Influência do lantânio nas propriedades estruturais do SrSnO3 - Cassia-santos, M. R. (2014)
The tin compounds with perovskite structure have shown promising properties for use as electronic ceramics such as sensors, catalysts and most recently, photoluminescent materials. In this work the effect of lanthanum on the structural properties of La xSr1-xSnO3 and the evaluation of this system as photoluminescent material were studied. The La xSr1-xSnO3 powders were synthesized by the polymeric precursor method and thermal treatments at 600, 800 and 1000 ºC for 4 h. The systems were characterized by thermal analysis, X-ray diffraction, specific surface area measurements, UV-Visible spectroscopy, infrared spectroscopy, scanning electron microscopy and photoluminescence measurements. X-ray diffraction analysis shows crystalline phase with cubic perovskite structure, as a function of calcination temperature for the additions of lanthanum (1, 5 and 10 mol%). Despite the addition of lanthanum in SrSnO3, the perovskite structure is stable. The crystallite size decreased with the addition of lanthanum, indicating that this dopant may be acting as a possible particle growth inhibitor and hence decreasing crystallite size. The results of the specific surface area show that the addition of lanthanum favors, in general, the formation of higher surface area solids. Values of the optical gap, according to the theory of Tauc, are between 3.81 and 3.98 eV, showing a gradual increase due to the addition of lanthanum. The powders doped with 1 mol% of lanthanum and treated at 600 ºC presented higher photoluminescent emission intensity.